2008
DOI: 10.1523/jneurosci.5100-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Gap Junction-Mediated Astrocytic Networks in the Mouse Barrel Cortex

Abstract: The barrel field of the somatosensory cortex constitutes a well documented example of anatomofunctional compartmentalization and activity-dependent interaction between neurons and astrocytes. In astrocytes, intercellular communication through gap junction channels composed by connexin 43 and 30 underlies a network organization. Immunohistochemical and electrophysiological experiments were undertaken to determine the coupling properties of astrocyte networks in layer IV of the developing barrel cortex. The expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
170
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(185 citation statements)
references
References 47 publications
13
170
2
Order By: Relevance
“…Biocytin morphological processing revealed that astrocytes were highly connected, as demonstrated by the spread of biocytin across many astrocytes (51.2 ± 5.0 cells), covering a total area of 65.8 × 10 3 ± 5.6 × 10 3 μm 2 ( Fig. 1E) (n = 12 slices), similar to previous results (24,25).…”
supporting
confidence: 88%
“…Biocytin morphological processing revealed that astrocytes were highly connected, as demonstrated by the spread of biocytin across many astrocytes (51.2 ± 5.0 cells), covering a total area of 65.8 × 10 3 ± 5.6 × 10 3 μm 2 ( Fig. 1E) (n = 12 slices), similar to previous results (24,25).…”
supporting
confidence: 88%
“…In the GL, GJC between astrocytes is preferentially confined within OG and thus overlaps neuronal organization. This feature results from at least two astroglial properties: (i) the oriented morphology of glomerular astrocytes processes toward the OG center (7)(8)(9) where most of the GL neuronal transmission occurs, and (ii) the enriched expression of the two astroglial Cxs within functional units, as already reported in the somatosensory cortex (25). In addition, the physical barrier formed by the somata of the juxtaglomerular neurons can also contribute to the gap in Cx expression observed around glomeruli (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Astrocytes are connected through the gap junction molecules connexin 43 (Cx43) and Cx30 (Anders et al, 2014; Chever et al, 2014; Pannasch and Rouach, 2013; Pannasch et al, 2011). Gap junctions might be involved directly or indirectly in synapse‐glia signaling (Houades et al, 2008). Recently, it has been reported that Cx43 mediates synaptic efficacy by setting the levels of synaptic glutamate in mice (Chever et al, 2014).…”
Section: Molecular Machineries Of Astroglial Morphogenesis: Volume Comentioning
confidence: 99%